Efficient cost management through excellence quality management practices among local authorities in Malaysia - Mohd Ali, Khairul Anuar; Jemain, Abdul Aziz; Yusoff, Rushami Zien; Abas, Zakaria (Taylor & Francis Group, 2007)
This study examines the relationship between quality management practices and the efficiency in cost management in Local Authorities.Eighty organizations participated in this study, whereby the data are gathered through self-administered structured questionnaire.Employing regression analysis, the results revealed that both employee focus and ICT have positive association with the efficiency in cost management while process management has the inverse relationship.Thus, in order to achieve a superior level of efficiency in cost management, Local Authorities need to address these three components.